The influence of compaction frequency on the skeleton characteristics of asphalt mixtures - Yichong Chen; Xianglin Lu; Junlin Zhou; Leizhou Cai; Cansheng Wang; Cheng Lu (Journal of Highway and Transportation Research and Development)
In order to understand the influence of compaction energy on the skeletal structure of dense-graded asphalt mixtures, it is essential to establish a stable skeletal framework. This study addresses the limitations of existing research regarding the effects of compaction energy on asphalt mixtures by analyzing the volumetric parameters of specimens subjected to varying compaction stages, specifically ranging from 25 to 1,000 gyrations. Digital image processing techniques are employed to investigate the microstructural characteristics of asphalt mixtures under different compaction energies. The results indicate: (1) For both Granite Asphalt Concrete (GAC) and Stone Matrix Asphalt (SMA) mixtures, the density initially increases rapidly, then slows down after 250 gyrations, without exhibiting a consistent trend. (2) Throughout the compaction process, the contact points and average coordination numbers of 4.75 mm aggregates in SMA mixtures surpass those observed in GAC mixtures. As compaction frequency increases, the contact points and average coordination numbers of coarse aggregates initially rise before subsequently declining, with some coarse aggregates becoming suspended within the fine aggregates. (3) By excluding the aggregates that do not make contact, the effective Voids in Coarse Aggregates (VCAeffect) are calculated to assess the skeletal changes within of the mixture. The SMA mixture demonstrates a more robust skeletal structure compared to GAC, with VCAeffect initially decreasing before increasing. As increase in the compaction frequency correlates with a rise in the number of no-contact coarse aggregates, ultimately leading to the degradation of the destruction of the skeletal structure of the asphalt mixture .